2019
DOI: 10.1016/j.ajem.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Approach to buprenorphine use for opioid withdrawal treatment in the emergency setting

Abstract: Opioid use disorder (OUD) is increasing in prevalence throughout the world, with approximately three million individuals in the United States affected. Buprenorphine is a medication designed, researched, and effectively used to assist in OUD recovery. Objective: This narrative review discusses an approach to initiating buprenorphine in the emergency department (ED) for opioid-abuse recovery. Discussion: Buprenorphine is a partial mu-opioid receptor agonist with high affinity and low intrinsic activity. Bupreno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 64 publications
(72 reference statements)
0
30
0
Order By: Relevance
“…In studies, initial induction doses ranged from 2 mg to 4 mg and up to a maximum of 16 mg over the ED course. 19,20,22,23,27,[31][32][33] Timing of buprenorphine administration included waiting 24 hours after the last known use of extended-release opioids, 27,31,32,34 6-12 hours after the last known use of short-acting opioids, 27,32,34 and 48 hours following the use of methadone after that agent had been substantially tapered. 34 No studies compared different induction regimens or different practices for subsequent dosing, so the optimal induction regimen for improving outcomes remains unknown.…”
Section: Optimal Procedures For Buprenorphine Inductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In studies, initial induction doses ranged from 2 mg to 4 mg and up to a maximum of 16 mg over the ED course. 19,20,22,23,27,[31][32][33] Timing of buprenorphine administration included waiting 24 hours after the last known use of extended-release opioids, 27,31,32,34 6-12 hours after the last known use of short-acting opioids, 27,32,34 and 48 hours following the use of methadone after that agent had been substantially tapered. 34 No studies compared different induction regimens or different practices for subsequent dosing, so the optimal induction regimen for improving outcomes remains unknown.…”
Section: Optimal Procedures For Buprenorphine Inductionmentioning
confidence: 99%
“…Research studies found these side effects to be relatively infrequent. Adverse effects of induction in the ED included precipitated withdrawal, 13,20,31,33,34 sedation, 31,34 QT prolongation (lengthening of a segment of the heart beat that can lead to arrhythmias), 31,32 and potential P450 medication interactions. 32 No studies reported adverse events during follow-up periods after the ED induction.…”
Section: Adverse Effects Of Inductionmentioning
confidence: 99%
See 2 more Smart Citations
“…D'Onofrio et al (2015) found that the ED initiation of B/n was cost-effective for patients with opioid use disorders (6). Following this landmark study, emergency physicians across the United States (Oakland, California; Camden, New Jersey; Syracuse, New York) and in Canada (Alberta and Ontario) have initiated programs that use the ED proactively to address the opioid epidemic by initiating treatment with B/n as part of opioid agonist therapy for opioid use disorders (8)(9)(10)(11). Other provinces in Canada, like Nova Scotia and British Columbia, have started a takehome naloxone programs from their EDs (12).…”
Section: Introductionmentioning
confidence: 99%